Решить: a/a-b - b/a+b a/b-a - b/a+b b/a-b - a/a+b

Решить: a/a-b - b/a+b a/b-a - b/a+b b/a-b - a/a+b
Гость
Ответ(ы) на вопрос:
Гость
a/ ( a - b ) - b/( a + b ) = ( a( a + b ) - b( a - b )/ ( a^2 - b^2 ) = ( a^2 + ab - ab + b^2 )/( a^2 - b^2 ) = ( a^2 + b^2 )/( a^2 - b^2 ) ••••••••••• a/( b - a ) - b/( a + b ) = ( a( a + b ) - b( b - a )) / ( b^2 - a^2 ) = ( a^2 + ab - b^2 + ab ) / ( b^2 - a^2 ) = ( a^2 - b^2 + 2ab )/( b^2 - a^2 ) •••••••••• b/( a - b ) - a/( a + b ) = ( b( a + b ) - a( a - b ))/( a^2 - b^2 ) = ( ab + b^2 - a^2 + ab )/( a^2 - b^2 ) = ( b^2 - a^2 + 2ab )/( a^2 - b^2 )
Не нашли ответ?
Ответить на вопрос
Похожие вопросы